Potential hepatic-protective effect of Physalis Peruviana against Lead-induced Toxicity in Albino Rats - Fatma Ismail; eglal Ghoneim; ossama Abdullatef; samar Aborhyem (International Journal of Public Health Science (IJPHS), 2022)
ABSTRACT Lead toxicity poses a serious threat facing humanity. This research aims to investigate the potential hepatoprotective effect of Physalis Peruviana (P.P.) fruit against lead toxicity (10ppm (1/45 LD50)) in male albino rats. Toxicological induction lasted for 28 days followed by treatment with 200, 300, and 500 mg/kg of lyophilized P.P. fruit extract for another 28 days. Antioxidant enzymes including; SOD, MDA, CAT, and GSH using a spectrophotometer and lead concentration in liver tissues were assessed using Atomic Absorption Spectroscopy after 4 and 8 weeks, in addition to liver function ALT and AST, and CBC.  Lead acetate induced substantial elevation in MDA levels, and a significant decrease in SOD, CAT, and GSH activities. Treatment with 200, 300, and 500 mg/kg P.P extracts showed an improvement in the activity of the antioxidant enzymes in a dose-dependent manner. Co-administration of P.P fruit extract ameliorates the damage caused by lead acetate. Physalis Peruviana solution showed a reduction in the mean lead concentration in a dose-dependent response to 0.26±0.02, 0.21±0.02, and 0.14±0.03 ppm for groups III, IV, and V, respectively. In conclusion, P.P fruit extract can induce antioxidant activity and exert a beneficial effect for the treatment of Pb-induced hepatotoxicity.